2016
DOI: 10.4081/rt.2017.6942
|View full text |Cite
|
Sign up to set email alerts
|

Helical Tomotherapy® is a Safe and Feasible Technique for Total Scalp Irradiation

Abstract: Angiosarcoma of the scalp is a rare aggressive tumor that affects elderly patients. Chemoradiation is the treatment of choice for multicentric and extensive disease. The shape of the scalp represents a dosimetric challenge in terms of achieving a homogeneous concave dose distribution with coverage of the entire target volume and an acceptable organs-at-risk sparing. We report a case of an 81-year-old man with a multifocal angiosarcoma of the scalp treated with Helical TomoTherapy® (Accuray Inc., Sunnyvale, CA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 11 publications
0
25
0
Order By: Relevance
“…In an attempt to address this problem, the advanced technique of intensity-modulated radiation therapy (IMRT) is currently being utilized for total scalp irradiation in some institutions. In particular, some clinical studies concerning helical tomotherapy and rotational IMRT, typified by volume-modulated radiation therapy, have reported an excellent dose distribution that is homogeneous over the whole scalp while reducing the irradiated dose and volume given to organs at risk, such as the central nervous system (28)(29)(30). Although insufficient clinical data on patients treated with such advanced techniques have thus far been collected, these are novel and promising tools for total scalp irradiation.…”
Section: Future Prospectsmentioning
confidence: 99%
“…In an attempt to address this problem, the advanced technique of intensity-modulated radiation therapy (IMRT) is currently being utilized for total scalp irradiation in some institutions. In particular, some clinical studies concerning helical tomotherapy and rotational IMRT, typified by volume-modulated radiation therapy, have reported an excellent dose distribution that is homogeneous over the whole scalp while reducing the irradiated dose and volume given to organs at risk, such as the central nervous system (28)(29)(30). Although insufficient clinical data on patients treated with such advanced techniques have thus far been collected, these are novel and promising tools for total scalp irradiation.…”
Section: Future Prospectsmentioning
confidence: 99%
“…The posterior double‐shell bolus is fixing the patient to the baseplate onto the Treatment coach. With the use of DSB technique, we achieved good dose homogeneity and conformity of the PTV and lower doses to the OAR, especially mean dose of the brain compared to the published data . Without the DSB application, the PTV can definitely exceed the patient's skin outline due to tumor invasion at the skin.…”
Section: Discussionmentioning
confidence: 70%
“…The main goal of this study was to provide a uniform dose (with the desired skin coverage) to the target (scalp/skull) while maintaining the dose delivered to the normal tissues as low as possible (compared to the published data) using linac based VMAT technique. This therapeutic goal cannot be easily achieved without the use of the DSB device because of the concave shape of the target, lesion at the skin (the objective was 100% coverage of the skin), and the doses to the OARs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Helical tomotherapy (HT) has also been shown to be a reasonable radiation therapy technique for TSI, owing to its ability to deliver tangential beams to any point on the scalp with no need for field matching [10][11][12][13]. Song et al [9] performed a dosimetric comparison of HT to 3DRT and VMAT and found that HT provided the best conformality of all 3 techniques and resulted in the lowest mean brain dose.…”
Section: Introductionmentioning
confidence: 99%